JUVENILLE DELINQUENCY IN ISLAMIC EDUCATIONAL PSYCHOLOGY PERSPECTIVE - azam syukur rahmatillah (Jurnal Ilmiah Pesantren, 2017)
The theme of juvenile delinquency is not really a weird theme, but the theme is already become history, even since the time of prophecy. As proof, there are the children of prophet when still a teenager growing up become adult that showed delinquency and disobedience to parents. This further reinforces that the delinquency and juvenile delinquency is a classic to the contemporary era which is still growing even at the level of alert. In essence, if certain parties that in this case the parents, educators, and the family learned of his knowledge, they are juvenile could have been avoided and overcome, namely by developing “aspects of seeding affection, pure unconditional” to children-teenagers, because his life children, adolescents misses the bigger the attention and affection more than his parents. Unfortunately, not many parents who are able to develop nurseries with pure love unconditionally.